Postsynthetic Covalent Modification in Covalent Organic Frameworks. Issue 9 (26th July 2018) - Yusran, Yusran; Fang, Qianrong; Qiu, Shilun
Abstract: The modification of covalent organic frameworks (COFs) based on postsynthetic covalent linkages is discussed in this review. In this strategy, the COF is preparedas scaffold and then assembled with functional groups with preservation of structural skeleton. Recent studies indicate that a number of COFs, such as COF‐5 and 3D‐OH‐COOF, are controllable to postsynthetic modification. Furthermore, covalentmodifications including triazole, ester, amide, sulfide, o ‐carbamate, ether, and oxime are suitable for postsynthetic functionalization. The rapid development of postsynthetic modification demonstrates that this approach will provide a general platform to create COFs as robust functional porous materials for wide applications. Abstract :